Matemáticos da Selva: A Digital Game for Teaching Mathematics in Middle School - Sousa, Hiago Henrique de; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
This paper presents the development and application of Matemáticos da Selva, a digital educational game focused on teaching mathematics to middle school students. Developed using Unity3D, the game aims to provide an engaging and enjoyable way to teach mathematics. In the game, players use the help of animals to defend forests from monsters threatening to destroy them, and through mathematical knowledge, they gain benefits to ensure the forests' safety. Matemáticos da Selva was tested in a school with a class of 22 students and demonstrated positive results as an educational tool, contributing to the use of digital games in teaching.